The relationship between graduation school background and geographical distribution of dentists in Taiwan - Feng-Chou Cheng; Tzu-Chiang Lin; Ling-Hsia Wang; Wen-Juain Lin; Ming-Chung Lee; Chun-Pin Chiang (Elsevier, 2024)
Background/purpose: Taiwan's eight dental schools are all located in the western region. This study attempted to analyze the relationship between the geographical distribution of dentists in Taiwan and their graduation school background and to develop several statistical indicators to analyze the geographical distribution of dentists. Materials and methods: The method of the secondary data analysis was adopted to collect the open information related to the number of the practicing dentists based on their graduation schools and practice locations by cities and counties in Taiwan in January 2023. The data were used to develop several statistical indicators to analyze the geographical distribution of dentists. Results: There were 16,533 practicing dentists in Taiwan in January 2023. Of the 16,533 dentists, 15,687 (94.88 %) graduated from domestic dental schools and 846 (5.12 %) graduated from foreign dental schools. For the school location, the coefficient of variation, Gini coefficient, population proportion index, and population density index were the largest (168.57 %, 0.47, 10.76 %, and 3927.01 people/square kilometer) in the dentists graduating from the northern dental schools. In overall, the dentists were concentrated in municipalities, cities, and the northern region of Taiwan, especially those graduating from the northern dental schools. Conclusion: In Taiwan, the geographical distribution of dentists is highly related to their graduation school background. Promoting a balanced distribution of dental enrollment quotas and dental student sources from different geographical locations and inducing the movement of dentists to the dentist-shortage areas may be the more feasible ways to solve the uneven geographical distribution of dentists in Taiwan.